Abundance of plastic microbeads in Hong Kong coastal water. (August 2018) - So, Wing Kwan; Chan, Kayi; Not, Christelle
Abstract: To address the rising concern over the use of plastic microbeads in personal care and cosmetic products, countries worldwide have started taking legislative actions to ban microbeads. Yet, the degree of contamination of coastal waters by plastic microbeads is rarely reported. Surface manta trawls were conducted to investigate the presence of microbeads in the southern coastal waters of Hong Kong. Considering only the size fraction of 0.3 to 1 mm, 60% of samples were found to contain microbeads. Microbeads accounted for 3.6% of the total microplastics collected and microbead abundance ranged from 0 to 380, 129 pcs/km 2 . The shapes, sizes, colours, and composition of microbeads found in our samples were similar to those from tested facial scrubs, suggesting that pelagic microbeads collected in this study very likely originated from the cosmetic products available locally. Microbeads represent a non-negligible part of the microplastics found in surface coastal waters. Highlights: Microbeads are a non-negligible part of microplastic found coastal water. Microbeads from cosmetic and personnel care products are found in oceanic surface water. Extreme weather events increase the abundance of microbeads in coastal water.